The need for contextual intelligence in athletic training - Kutz, M. R. (International Journal of Athletic Therapy & Training, 2022)
Athletic training and the environment in which it is practiced is constantly changing. The emergent environment is volatile, uncertain, complex, and ambiguous. This new environment necessitates an adjustment to athletic training education particularly as it pertains to the instruction and development of the nonclinical skills (meta-skills) needed for clinical settings. One such meta-skill is contextual intelligence. Contextual intelligence is the capacity to recognize the convergence of different variables and respond to the emerging context as it is developing. Practicing contextual intelligence includes integrating 12 specific behaviors and the 3D thinking framework of hindsight, insight, and foresight into clinical decision making.